Experience of CBT in adults with ADHD: a mixed methods study - William, Sandy; Horrocks, Matthew; Richmond, Jemma; Hall, Charlotte L.; French, Blandine (Frontiers in Psychiatry, 2024)
Introduction The National Institute for Health and Care Excellence (NICE) recommends Cognitive-Behavioural therapy (CBT) as the psychotherapeutic treatment of choice for adults with Attention Deficit Hyperactivity Disorder (ADHD) in the UK. However, the literature often refers to adapted CBT programs tailored for ADHD and provides limited insight into how adults with ADHD experience and perceive this form of treatment in routine clinical practice. Methods This mixed-methods study aims to explore ADHD individuals’ experience and perception of CBT delivered in routine clinical practice, to gain a better understanding of this treatment’s helpfulness and perceived effectiveness. Results A survey (n=46) and semi-structured in-depth interviews (n=10) were conducted to explore the experience of CBT and its perceived effectiveness in managing ADHD. The interviews were analysed using thematic analysis and the survey was synthesised using descriptive narratives. The thematic analysis highlighted three key themes: difficulties with the CBT framework, difficulties with CBT therapists, and consequences of CBT. The survey highlighted similar findings. Participants described the CBT framework as, generic, rigid, and too short, and described the CBT therapist as unspecialised, unempathetic, and not sufficiently adapting CBT to ADHD-related difficulties. Discussions Overall, participants found non-adapted, generic CBT in the UK to be unhelpful, overwhelming, and at times harmful to their mental well-being. Therefore, it is necessary for clinical bodies in the UK, while following the indicated NICE guidelines, to be mindful of adapting CBT delivery of CBT, to be most effective for people with ADHD and to mitigate potential harm.